Pengaruh e-LKPD Berbasis Keterampilan Proses Sains terhadap Hasil Belajar, Motivasi Belajar, dan Kemampuan Metakognitif Peserta Didik Kelas XI SMA - Adnan Adnan; Suhardi Aldi; Akhmad Faqih Dzulkarnain; Sitti Marliyah (BIOEDUSCIENCE, 2022)
Background: This research is a quasi-experiment whose research design is a posttest-only control group design. This study aims to see the effect of e-LKPD based on science process skills in terms of learning outcomes, learning motivation, and students' metacognitive. All students in class, XI MIPA SMAN 14 Makassar from five classes make up the population. Method: The technique used in taking samples of this research is random sampling. There were 28 students of class MIPA 2 and 28 students of XI MIPA 4 who became the control action as a sample. The test instrument is in the form of multiple choice to assess the ability of learning outcomes and the use of questionnaires in measuring learning motivation and questionnaires to measure students' metacognitive abilities. This study's data analysis technique is a descriptive and inferential statistical analysis using non-parametric tests (Mann Whitney). The descriptive analysis results illustrate that using e-LKPD based on science process skills (KPS) for students has learning outcomes in the high category, a very high category in learning motivation, and metacognitive abilities in the high category. Results: The results of the inferential analysis illustrate significant differences in learning outcomes, learning motivation, and metacognitive abilities of students using KPS-based e-LKD in the experimental class, with the mean rank value in the experimental class being higher than the control class. Conclusion: The results of the KPS-based e-LKPD research significantly influence learning outcomes, learning motivation, and students' metacognitive abilities in biology learning at SMA Negeri 14 Makassar.